Inﬂuence of UV irradiation on mechanical properties and structures of sol–gel-derived vinylsilsesquioxane ﬁlm - Ainuddin, Ainun Rahmahwati; Ishigaki, Tomonori; Hakiri, Norio; Muto, Hiroyuki; Sakai, Mototsugu; Matsuda, Atsunori (The Ceramic Society of Japan, 2012)
The inﬂuence of ultraviolet (UV) irradiation on vinylsilsesquioxane (ViSiO3/2) ﬁlms was investigated using a nanoindentation technique, and the structural changes were analyzed. Solid-state 13C cross-polarization magic-angle-spinning nuclear magnetic resonance and infrared spectra of the ﬁlms conﬁrmed the polymerization of C=C bonds and formation of a CC bridge structure upon UV irradiation. Since the vinyl group is a photosensitive organic component with a short organic chain, it is expected to show a large improvement in mechanical properties as a result of the formation of an organic network under the inﬂuence of UV irradiation. It is shown that varying the intensity of the UV irradiation leads to changes in the hardness and elasticity. The irradiation energy was found to determine the mechanical properties of the ViSiO3/2 ﬁlms, regardless of the effects of different UV intensities on the hybrid ﬁlms.